Challenges and opportunities of livestock development in Hot Arid Zone of India (Indian Journal of Animal Production and Management, 2024)
Arid regions constitute 12% of total geographical area of India ranging from cold arid areas in northern  parts to hot arid areas in western and southern parts of country. Climatic stresses (drought, extreme  temperatures, sand blasting), edaphic factors (sandy soil with low organic carbon content and poor water  holding capacity), and relatively higher biotic pressure (human and livestock population) in these areas are  major contributing factors to degradation of natural resources and lower productivity resulting in greater  risk of farming per se. The farming systems in hot arid zone are quite diverse with a variety of crops and  cropping systems, agroforestry and livestock. Livestock production is an important component in arid zone,  as it is considered an instrument to socio-economic change to improved income and quality of life with  equity. The sustainable development in arid zone can only be achieved through optimum utilization of its  natural resources. Though technologies to improve livestock productivity do exist, however, the awareness  and rate of adoption of technologies in arid production systems is consistently low, because of the existing  research and extension set up and related other constraints. There is tremendous scope of increasing  livestock productivity of indigenous breeds by improving nutrient availability from locally available feed  and fodder resources. The long term sustainability and profitability of livestock production system depends  largely on how efficiently the farmer manages his limited resources. The paper discusses the status of  livestock production systems in hot arid zone of India, contribution to farmer’s livelihood, challenges and  future strategies to make livestock farming in arid regions more profitable and resilient to climatic stress.